ATMOSFER AKADEMIK DAN PERFORMANSI INTELEKTUAL DUNIA KAMPUS SEBAGAI EFFORT KEMAJUAN DUNIA PENDIDIKAN ISLAM - Mohammad Subhan; Abd Haris (Fakultas Agama Islam Universitas Islam Madura, 2023)
The academic atmosphere and intellectual performance in the world of education, which in this case is the campus as a trigger for the advancement of the world of education, is the dream of education practitioners for the advancement of national civilization. Therefore, it is the duty and responsibility of campus practitioners, in this case the campus managers and lecturers have performed as expected, meaning that as educators and science developers it is appropriate for them to start and fulfill these obligations, therefore researchers are interested in researching and exploring this issue so that later it will become a bit of a contribution to the development of the world of education. The research method in this research activity the researchers used library research and which was used as a source of data in this study was literature that had a relationship with the theme and current research studies and the researchers found in the field. The results of the study show that there are several values ​​for the development of an academic atmosphere that can be developed by campus managers, which include the value of responsibility, the value of honesty, the value of criticality, the value of perseverance and the value of knowing and caring. The implication of this research is that people can know that the academic atmosphere and performance are driving the progress of the world of Islamic Education, so that concern for the progress of Islamic Education can be increased.